2019
DOI: 10.1002/app.48299
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency preparation of polypropylene nanofiber by melt differential centrifugal electrospinning

Abstract: Melt differential centrifugal electrospinning (MDCE) method is proposed by integrating the advantages of centrifugal spinning and melt differential electrospinning, including high efficiency, solvent-free, multiple jets formation from nozzle-less spinning system, and small diameter. A mathematical model of jet diameter in MDCE is established. An orthogonal experiment is carried out to explore the effects of main processing parameters on the average diameter and the diameter standard deviation of the prepared f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…In this regard, there are a few works devoted to electrospinning from polypropylene solutions: it is reported that nonwovens were produced from solutions in decalin [ 9 ] or from mixtures of solvents based on decalin [ 10 ] and cyclohexane [ 11 ], while heating the solution to 70–130 °C was required to dissolve the polymer. On the other hand, it is possible to produce fibrous polypropylene materials from the melt by electrospinning [ 2 , 3 , 4 , 5 , 7 , 8 , 9 , 12 , 13 , 14 ], melt-blowing [ 1 , 15 ], centrifugal spinning [ 16 ] or by combining several of these methods [ 17 ]. Moreover, nonwovens can be produced, not only from polypropylene homopolymers, but also from its copolymers [ 18 ] and blends with other polymers [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, there are a few works devoted to electrospinning from polypropylene solutions: it is reported that nonwovens were produced from solutions in decalin [ 9 ] or from mixtures of solvents based on decalin [ 10 ] and cyclohexane [ 11 ], while heating the solution to 70–130 °C was required to dissolve the polymer. On the other hand, it is possible to produce fibrous polypropylene materials from the melt by electrospinning [ 2 , 3 , 4 , 5 , 7 , 8 , 9 , 12 , 13 , 14 ], melt-blowing [ 1 , 15 ], centrifugal spinning [ 16 ] or by combining several of these methods [ 17 ]. Moreover, nonwovens can be produced, not only from polypropylene homopolymers, but also from its copolymers [ 18 ] and blends with other polymers [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, the preparation method for nanofibers based on electrospinning technology has been well developed. According to the electrospinning raw materials, it can be divided into melt electrospinning [46][47][48], solution electrospinning [49,50] and mixed electrospinning [51][52][53]. According to the design of the spray head, it can be classified as needleless electrospinning [54][55][56], coaxial or triaxial electrospinning [57][58][59][60][61][62], multi-jet electrospinning [63][64][65], etc.…”
Section: Strategies For the Preparation Of Functional Electrospun Matmentioning
confidence: 99%
“…This driving force is exacerbated when an electric field is applied. Several papers have addressed this topic, and it seems to be the only area where there is a consensus—regardless of whether it is solution or melt electrospinning, gravity is so weak compared with the centrifugal force that its effects are negligible [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: State Of the Art—impact Of Apparatus Orientation In Electmentioning
confidence: 99%